Development of a Novel Jig Design to Reduce Fabrication Time of Metal Parts - S. K. S. Kumar; R. D. S. G. Campilho; F. J. G. Silva (Research and Developments in Engineering Research Vol. 4, 2023)
Machining is the most prevalent manufacturing operation in terms of volume and expenditure. Machining operations of complex parts need to be properly thought in order to save time and improve the competitiveness of the parts. Often, jigs and fixtures are overlooked in milling processes, as an auxiliary tool, but these can help in optimizing a machining process as a part of continuous improvement. The method used for this study was base an increasing demand forecast of a complex part, called Winding cone, which implies a reduction in the takt time from 4.6 to 2.6 minutes per part. This research tries to establish the best solution for the project, which was divided into four phases: research, design, machining, and implementation. The design phase was based on the methodology of Design for Six Sigma methodology (DFSS) for the fixture. The project’s critical outputs were harvested during the implementation phase. The newly designed and produced modular jig system is able to deal with 12 parts per cycle, proving to be able to increase the number of parts machined per day by 32%, with expected savings of more than €6000 per year. This drastically reduces the lead times for new parts, which is crucial for a small-medium enterprise stay competitive. The new jig design and fabrication allowed comfortable loading and unloading of parts.